Hindu Woman as an Individual Self and a Social Institutional Self (Socio-Economic Development Panorama, 2009)
This article explores various religious forms of portraying a socially individual Hindu woman's status in reference to the present educational and developmental context. In doing so, the research attempts to highlight a Hindu woman's culturally sensitive image, as a patibrata wife or glorious mother in her society. This article has also brought forth various crosscutting dichotomies in women's issues that are critical to its socio-cultural status. In the same way, the article suggests measures to embrace cultural sensitiveness of a Hindu woman while bringing her agenda in the floor of social discussion.The effect of this phenomenon has created an unbalanced socio-cultural environment in which women's wisdom or inheritances of feminine values were forcefully suppressed by men's rational knowledge or masculine value systems. Thrusting this argument, it underlines how such an imbalance inevitably invites social and natural disaster in the world. This factor itself might become a prominent cause of an erosion of patriarchy culture in the long run.The practical source of Hindu patriarchy is quite different from Hindu religious literatures. The focus put forward by religious texts have advocated the role of a man and a woman differently (Bhandari, 2008). These texts have portrayed the characters of men as perfect, absolute, brave, courageous, aggressive, controller of the spatial hierarchy and ruler; and women as being shy, passive, submissive, subservient one.Key words: Individual woman; social woman; patriarchy; patibrata; kinswomen; sasu and buhariSocio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June.